Pengaruh kualitas produk, persepsi harga dan promosi terhadap kepuasan konsumen dan terhadap keputusan pembelian pada online shop JD.ID - Lestari, Rahayu; Fengyuan , Liao (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
In this era of globalization, technology, which adds value, is universally accepted in our global society. Instagram, Facebook, Twitter, and more come online with technology. This study aims to examine how product quality, price perceptions, and promotions affect customer satisfaction and purchase choices at the JD.id online store. Purposive sampling selected 272 workers for the study. The questionnaire collects data, which SEM analyzes. Product quality, price perceptions, and promotions have a positive effect on consumer satisfaction at the JD.id online store, according to the study. JD.id buyers are influenced by product quality, price perceptions, and promotions. JD.com buyer satisfaction has a positive impact on their purchases. Product quality, price perceptions, and promotions indirectly influence purchase choices through customer satisfaction.